2014
DOI: 10.12691/ajmbr-2-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Haematological Indices in Auto-Mechanics and Fuel Attendants in Elele Nigeria

Abstract: Gasoline is largely a mixture of hydrocarbon and hydrocarbon consists of mixture of n-paraffins, naphthalene, olefins and aromatics. Aromatics is mostly a mixture of benzene, toluene and xylene. Fuel attendants and auto mechanics are exposed to gasoline either by direct contact or inhalation. The effect of this exposure in fuel attendants and auto mechanics is determined using haematological parameters. 35 fuel attendants and 35 auto mechanics were used as test group and compared with 30 apparently healthy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
(11 reference statements)
2
16
1
Order By: Relevance
“…Accordingly, Okoro et al [20] observed time-dependent significant decreases in red blood cell (RBC) count, white blood cell (WBC) count, hemoglobin (Hb), mean corpuscular concentration (MCHC), mean cell volume (MCV), and mean cell hemoglobin (MCH) among 200 exposed gasoline station workers at Calabar. A recent study by Ajugwo et al [6] in Elele in Nigeria made a similar observation. Likewise, studies by Qu et al [19] and Aleemuddin et al [25] showed significant decreases in RBC, WBC and neutrophil counts among workers exposed to gasoline compounds.…”
Section: Hematoxicitysupporting
confidence: 62%
See 3 more Smart Citations
“…Accordingly, Okoro et al [20] observed time-dependent significant decreases in red blood cell (RBC) count, white blood cell (WBC) count, hemoglobin (Hb), mean corpuscular concentration (MCHC), mean cell volume (MCV), and mean cell hemoglobin (MCH) among 200 exposed gasoline station workers at Calabar. A recent study by Ajugwo et al [6] in Elele in Nigeria made a similar observation. Likewise, studies by Qu et al [19] and Aleemuddin et al [25] showed significant decreases in RBC, WBC and neutrophil counts among workers exposed to gasoline compounds.…”
Section: Hematoxicitysupporting
confidence: 62%
“…Several epidemiological studies [6,[16][17][18][19][20][21] have established a close association between exposure to gasoline compounds and hematoxicity for humans. Although the reports of its effects on specific blood cells have been somewhat inconsistent, gasoline hematoxicity appears to be a constant feature and has been observed even at levels previously considered harmless to humans [22][23][24].…”
Section: Hematoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The insignificant effect of fuel exhaust exposure to the chosen hematological factors may indicate that the dose and duration of exposure to the genotoxicant is not that high to cause an effect on DNA damage. Length/duration of exposure was pointed out by Ajugwo et al (2014) as the most probable factor that causes the reduction in RBC (Red blood cell count), WBC (White blood cell count), PCV (Packed cell volume), Hb (Haemoglobin concentration), MCV (Mean cell volume), MCH (Mean cell haemoglobin) and MCHC (Mean cell haemoglobin concentration) in fuel attendants and auto mechanics exposed to gasoline fumes.…”
Section: Discussionmentioning
confidence: 99%